Viral Marketing and Revisit Intention at Pacu Jalur: Brand and Destination Image Mediation - Diski Mulyadi; Gatot Wijayanto; Abd. Rasyid Syamsuri (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the effect of viral marketing on revisit intention with brand image and destination image as mediating variables at the Pacu Jalur cultural tourism event in Kuantan Singingi Regency, Riau. Using an explanatory quantitative approach, data were collected through questionnaires from 150 respondents selected via purposive sampling. Data analysis was conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with SPSS and SmartPLS software. The results indicate that viral marketing has a positive and significant direct effect on brand image, destination image, and revisit intention. Furthermore, both brand image and destination image significantly mediate the relationship between viral marketing and revisit intention. These findings confirm that viral promotion strategies on social media not only trigger instant revisit interest, but also effectively strengthen cultural identity and destination perception in the long term. Local government and organizers are advised to improve physical infrastructure facilities to perfect the digitally established destination image.